THE ROLE OF PANCASILA EDUCATION TEACHERS IN OVERCOMING BULLYING IN CLASS VLLL STUDENTS AT SMPN 2 WEST KARAWANG - santi; Fitri Silvia Sofyan; Erwin Susanto (Journal Civics And Social Studies, 2024)
This research falls within the category of descriptive qualitative studies. This research was carried out at SMPN 2 West Karawang. The subjects in this research were Pancasila Education teachers and class VIII students. Methods such as observation, interviews, and documentation are employed in data gathering approaches. In data analysis approaches, data reduction, data display, and the derivation of conclusions are encompassed. Based on the results of this research, bullying for students that occurs in class is students who mock and make fun of their friends by calling their friends by their parents' names. The role of Pancasila Education teachers in overcoming bullying is by reprimanding students and advising students so that students do not bully again. The role of Pancasila Education teachers in overcoming bullying can provide classical and individual guidance. Pancasila Education Teachers can coordinate with students' parents to advise students who bully. Keywords: The Role of Teachers, Overcoming Bullying, Pancasila Education